PELATIHAN PENULISAN KREATIF DALAM MENINGKATKAN KETERAMPILAN DI DESA SINDANGSARI - Sari, Veni Tiyas; Khadijah, Siti; Marginingsih, Ria (Universitas Islam 45 Bekasi, 2023)
Writing activities are basically good activities for children to do. By writing, children's creativity can be increased and a child is like immersing himself in the creative process which means the child creates something which also means asking questions, experiencing doubts and confusion until finally finding a solution. And when the creative process is increasingly practiced, it becomes easier for children to transfer their skills to other fields that also require creative solutions, such as school and other activities. From the results of observations of junior high school children and adolescents in the village of Sindangsari, Cabangbungin District, Bekasi Regency. has a high interest in reading short stories and is quite interested in trying to write stories, but there are still some children who have minimal interest in reading and writing, therefore the writer is interested in helping them develop their abilities and express feelings through writing stories in the service of the writer's KKN It is hoped that it can attract children's interest and motivation to write by using an approach that emphasizes the importance of the learning process for students, namely Story Telling or Reading stories, and Writing Training.